Better Remedies For Bad Exams: correcting for difficult questions in a fair and systematic way - Camenares, Devin (International journal for the scholarship of teaching and learning, 2022)
Balancing assessment of learning outcomes with the expectations of students is a perennial challenge in education. Difficult exams, in which many students perform poorly, exacerbate this problem and can inspire a wide variety of interventions, such as a grading curve. However, addressing poor performance can sometimes distort or inflate grades and demotivate students. Here, I review this problem and propose solutions which are fair and based upon item analysis of an assessment. To correct for exams with questions that were more difficult than intended, item score and discrimination is used to determine a bonus value in a way that is limited and continuous. Educators that utilize item analysis to improve exams for future iterations can easily use this approach to retroactively lessen the burden of some questions. This solution expands the repertoire of tools for achieving a transparent, fair, and equitable means of assessment.